Regulatory Role of Immune Cell-Derived Extracellular Vesicles in Cancer: The Message Is in the Envelope - Li, Chi; Donninger, Howard; Eaton, John; Yaddanapudi, Kavitha (Frontiers in Immunology, 2020)
Extracellular vesicles (EVs) are a heterogenous group of membrane-surrounded structures. Besides serving as a harbor for the unwanted material exocytosed by cells, EVs play a critical role in conveying intact protein, genetic and lipid contents that are important for intercellular communication. EVs, broadly comprised of microvesicles and exosomes, are released to the extracellular environment from nearly all cells either via shedding from the plasma membrane or by originating from the endosomal system. Exosomes are 40–150 nm, endosome-derived small EVs (sEVs) that are released by cells into the extracellular environment. This review focuses on the biological properties of immune cell-derived sEVs, including composition and cellular targeting and mechanisms by which these immune cell-derived sEVs influence tumor immunity either by suppressing or promoting tumor growth, are discussed. The final section of this review discusses how the biological properties of immune cell-derived sEVs can be manipulated to improve their immunogenicity.